"Are you telling the truth?": Testing individuals' ability to differentiate between truth and deceit in soccer - Englert, Christoph; Schweizer, Geoffrey (Frontiers in psychology, 2020)
In the present paper, we tested the ability of individuals to judge correctly whether athletes are lying or telling the truth. For this purpose, we first generated 28 videos as stimulus material: in half of the videos, soccer players were telling the truth, while in the other half, the same soccer players were lying. Next, we tested the validity of these video clips by asking N = 65 individuals in a laboratory experiment (Study 1a) and N = 52 individuals in an online experiment (Study 1b) to rate the level of veracity of each video clip. Results suggest that participants can distinguish between true and false statements, but only for some clips and not for others, indicating that some players were better at deceiving than others. In Study 2, participants again had to make veracity estimations, but we manipulated the level of information given, as participants (N = 145) were randomly assigned to one of three conditions (regular video clips, mute video clips, and only the audio stream of each statement). The results revealed that participants from the mute condition were less accurate in their veracity ratings. The theoretical and practical implications of these findings are discussed.